PENINGKATAN HASIL BELAJAR IPS TENTANG SISTEM ADMINISTRASI WILAYAH INDONESIA MELALUI STRATEGI PEMBELAJARAN DRILL REVIEW PAIRS (DRP) SISWA KELAS VI SDN MOJOREJO JETIS PONOROGO - Wijayatiningsih, Tutik (Educatio Vitae, 2016)
The research entitled “The Improvement of The Results of The Study of Social Sciences in The Topic of Administration System of Indonesian Area through The Learning Strategy of Drill Review Pairs (DRP) of The Sixth Graders of Mojorejo State Primary School of Jetis Ponorogo in Semester I 2012/2013 Academic Year” is a class act research towards 15 students which is conducted in 3 cycles consisting of 6 meetings. Each meeting consists of 2 X 35 minutes. Every cycle includes the activities of planning, implementation, observation, and reflection. The data are taken by using test instruments, interviewing, distributing questionnaires and journals. The aim of the research is to know the improvement of learning achievement. The role of Drill Review Pairs (DRP) learning model in improving the learning competence is noticed by the improvement of mean score starting from the first cycle until the last cycle which consists of 73.27 in cycle I: 79.87 in cycle II; and 84.00 in cycle III. The learning accomplishment is improving as well from 73.33% in cycle I, 86.67% in cycle II and 100% in cycle III. The research proves that the use of the learning model of Drill Review Pairs (DRP) in the process of learning could improve the learning achievement in the subject of Social Sciences in the sixth graders of Mojorejo State Primary School in Jetis, Ponorogo Regency. Key Words: Learning Achievement, Drill Review Pairs (DRP), Social Sciences